EVALUATION OF ANTIOXIDANT AND ANTICANCER ACTIVITIES OF CIPADESSA BACCIFERA - RAJANI, POBBA; M, RAMA KOTAIAH; KN, JAYAVEERA; KB, CHANDRA SEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study was conducted to evaluate the antioxidant and anticancer activities of methanolic extract of Cipadessa baccifera leaves. Methods: The total phenolic content in the extract was assessed by using Folin–Ciocalteu reagent. Antioxidant activity was assesses by different methods such as phosphomolybdate assay, ferric reducing power, 1,1-Diphenyl-2-picryl-hydrazyl, superoxide scavenging assay. Cytotoxic potential of the extract against Ehrlich Ascites carcinoma (EAC), colon carcinoma (HT-29), and breast adenocarcinoma (MCF-7) cell lines was evaluated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide assay. Results: The total phenolic content present in the methanolic extract of C. baccifera was found to be 338.38 mg GAL/L. In phosphomolybdate assay, C. baccifera extract showed good antioxidant activity (half maximal inhibitory concentration [IC ]=0.42 mg/ml) which was comparable to the standard ferulic acid (IC 50 =0.22 mg/ml). The extract showed better cytotoxicity against EAC (IC 50 50 3 =4.22 mg/ml) and HT-29 cell lines (IC =1.86 mg/ml) compared the MCF-7 cell lines (IC 50 =34.28 mg/ml). Conclusion: The extract showed good radical scavenging activity and anticancer activity against EAC and HT-29 cell lines. However, the activity was less compared to the standard. Further analysis is required to confirm the in vivo activity of the extract. The extract showed negligible cytotoxic effect against MCF-7 cell lines. Keywords: Anticancer, Antioxidant, Methanolic extract, Cipadessa baccifera, Radical scavenging, 1,1-Diphenyl-2-picryl-hydrazyl assay, Ehrlich Ascites carcinoma, HT-29, MCF-7.